Solution and Stability of a General Mixed Type Cubic and Quartic Functional Equation - Xiaopeng Zhao; Xiuzhong Yang; Chin-Tzong Pang (Journal of Function Spaces and Applications)
We consider the following mixed type cubic and quartic functional equation = where is a fixed integer. We establish the general solution of the functional equation when the integer , and then, by using the fixed point alternative, we investigate the generalized Hyers-Ulam-Rassias stability for this functional equation when the integer .